The Effect of Proportion Pulp and Albedo Yellow Kepok Bananas on the Characteristics of Sliced Jam with Various Concentrations of Sucrose - Vikri Furkhoni Iqbal; Ratna Yulistiani; Winarti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aimed to determine the effect of the proportion of pulp-albedo yellow kepok bananas and the concentration of sucrose on the characteristics of sliced jam. The study used a completely randomized design (CRD) with two factors and three replications. Data analysis used ANOVA followed by Duncan Multiple Range Test (DMRT) at 5% confidence level. The first factor was the proportion of pulp and albedo of yellow kepok bananas (1:2 (A1), 1:1 (A2), 2:1 (A3)). The second factor is the concentration of sucrose (30% (B1), 45% (B2), and 60% (B3)). Parameters observed included moisture content, ash content, pH, total sugar, water activity (aw), total dissolved solids, hardness, and organoleptic analysis, including taste, scent, color, and texture. The treatment results of the proportion pulp-albedo yellow kepok banana and the sucrose concentration significantly affected the water content, ash content, total sugar, total dissolved solids, hardness, and organoleptic tests. Sliced jam with the proportion of pulp-albedo yellow kepok banana (2:1) and sucrose concentration (60%) was the best treatment with 44.16% water content, 1.18% ash content, pH 4.03, total sugar 33, 21%, water activity 0.828, total dissolved solids 50, hardness 31.93N and the taste is quite typical of banana, quite smelly of banana, quite yellow in the color of banana, and has a firm texture.